Comparison of two protocols of periosteal distraction osteogenesis in a rabbit calvaria model. Issue 6 (2nd June 2015) - Saulacic, Nikola; Nakahara, Ken; Iizuka, Tateyuki; Haga‐Tsujimura, Maiko; Hofstetter, Willy; Scolozzi, Paolo
Abstract: The regenerative pathways during periosteal distraction osteogenesis may be influenced by the local environment composed by cells, growth factors, nutrition and mechanical load. The aim of the present study was to evaluate the influence of two protocols of periosteal distraction on bone formation. Custom made distraction devices were surgically fixed onto the calvariae of 60 rabbits. After an initial healing period of 7 days, two groups of animals were submitted to distraction rates of 0.25 and 0.5 mm/24 h for 10 days, respectively. Six animals per group were sacrificed 10 (mid‐distraction), 17 (end‐distraction), 24 (1‐week consolidation), 31 (2‐week consolidation) and 77 days (2‐month consolidation) after surgery. Newly formed bone was assessed by means of micro‐CT and histologically. Expression of transcripts encoding tissue‐specific genes (BMP‐2, RUNX2, ACP5, SPARC, collagen I α1, collagen II α1 and SOX9) was analyzed by quantitative PCR. Two patterns of bone formation were observed, originating from the old bone surface in Group I and from the periosteum in Group II. Bone volume (BV) and bone mineral density (BMD) significantly increased up to the 2‐month consolidation period within the groups ( p  < 0.05). Significantly more bone was observed in Group II compared to Group I at the 2‐month consolidation period ( p  < 0.001). Expression of transcripts encoding osteogenic genes in bone depended on the time‐point of observation ( p  < 0.05). Low level of transcripts reveals an indirect role of periosteum in the osteogenic process. Two protocols of periosteal distraction in the present model resulted in moderate differences in terms of bone formation. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1121–1131, 2016.